Reform of Sex Crimes in Japan - Rikizo, Kuzuhara (COLLECTION OF SCIENTIFIC WORKS OF SOKHUMI UNIVERSITY, 2023)
It should be noted that despite some criticism, the 2012 reform of sex crimes in the Criminal Code of Japan can be assessed positively overall. It is especially noteworthy the abolishment of the notion of „lewd acts“. Removing the restriction of the object of infringement only to women is a step towards the demoralization of sex crimes and safeguarding protection of sexual freedom. Removing the restriction of the object of infringement means making the sexual freedom of LGBT persons and of heterosexuals equal. This clarifies that the components of corpus delicti of the „lewd acts“ have been substituted by a restrictive list of „sexual intercourse, anal intercourse, or oral intercourse“, because all of them involve penetrating by male genitals; Only in such a case there is „sexual intercourse“. Corpus delicti of rape still does not include sexual acts between women. Hence, penetration by male genitalia distinguishes the rape from the coercion into acts of sexual nature. Two evaluative questions are asked at this time: Why does penetration have such a special meaning and why only by men? You will not find persuasive answers to these questions. There is neither empirically nor normatively justified reason to limit the punishability of rape to only particularly intensive use of violence or threat. If we consider that it is necessary for Japan to make punishable sexual acts committed without violence and threat, then it is recommended to introduce a new corpus delicti of the act punishable by a lenient sentence. The reform of sex crimes has sparked a debate that has been previously the subject of political debate only between feminists and conservatives. The amendments focus on the legal side of the issue, which is also one of the positive effects of the reform.